Evaluation of Serum S-100B Protein Levels in Patients with Simple Febrile Convulsions - Yetkin, İlhan; Shermatova, Kabil; Abuhandan, Mahmut; Demir, Mahmut; Aksoy, Nurten (Journal of Pediatric Neurology, 2016)
Objective This study aimed at evaluating serum S-100B protein levels after convulsions in children experiencing simple febrile convulsions.Material and Methods The study included 30 healthy children as the control group and 30 patients with simple febrile convulsions as the study group. Blood samples were obtained within 2 hours after the patients sustained febrile convulsions. Serum S-100B protein levels of the patients in the study group and the control group were measured using enzyme-linked immunosorbent assay kits.Results There was no statistically significant difference between the groups, when the mean serum S-100B protein levels were compared between patients with febrile convulsions and the control group (p > 0.05).Conclusion Lack of an increase in serum S-100B protein levels of patients with simple febrile convulsion suggests that febrile convulsive seizures do not cause any organ damage.
Keywords: simple febrile; convulsion; S-100B